Counselor Turnover in Substance Use Disorder Treatment Research: Observations from One Multisite Trial. Issue 2 (April 2019) - Hatch-Maillette, Mary A.; Harwick, Robin; Baer, John S.; Masters, Tatiana; Cloud, Kasie; Peavy, Michelle; Wiest, Katharina; Wright, Lynette; Beadnell, Blair; Wells, Elizabeth A.
Background: Counselor workforce turnover is a critical area of concern for substance use disorder (SUD) treatment providers and researchers. To facilitate the adoption and implementation of innovative treatments, attention must be paid to how SUD treatment workforce issues affect the implementation of clinical effectiveness research. Multiple variables have been shown to relate to turnover, yet reasons that are specific to conducting research have not been systematically assessed. Methods: In a randomized clinical trial testing a sexual risk reduction counselor training intervention, 69 counselors at 4 outpatient SUD treatment sites (2 opioid treatment programs [OTPs], 2 psychosocial) were enrolled and randomized to 1 of 2 training conditions (Standard vs. Enhanced). Study counselor and agency turnover rates were calculated. Agency context and policies that impacted research participation were examined. Results: Study turnover rates for enrolled counselors were substantial, ranging from 33% to 74% over approximately a 2-year active study period. Study counselor turnover was significantly greater at outpatient psychosocial programs versus OTPs. Counselor turnover did not differ due to demographic or training condition assignment. Leaving agency employment was the most typical reason for study counselor turnover. Conclusions: This secondary analysis used data from a multisite study with frontline counselors to provide a qualitative description of challenges faced when conducting effectiveness research in SUD treatment settings. That counselors may be both subjects and deliverers of the interventions studied in clinical trials, with implications for differential impact on study implementation, is highlighted. We offer suggestions for researchers seeking to implement effectiveness research in SUD clinical service settings.